Understanding The Role Of Nursing Interventions In Managing Diabetes Mellitus Complications (Journal of Namibian Studies : History Politics Culture, 2022)
Diabetes mellitus (DM) is a chronic disease that can lead to acute and chronic microvascular and macrovascular complications. These complications reduce quality of life and increase morbidity and mortality. Nursing plays a pivotal role in preventing and managing DM complications through patient education, support for self-management, preventive care, early identification and treatment of complications, and advocacy. This paper discusses common DM complications and evidence-based nursing interventions including patient teaching, foot care, cardiovascular risk reduction, blood glucose monitoring, medication administration, complementary therapies, and coordination of care. Implementing best practices enables nurses to optimize outcomes and quality of life for patients with this complex, lifelong disease.